c - d; d (b, 2008)
Index to articles on the liberation war of Bangladesh as reflected in 1971, in contemporary English newspapers published from various countries of the world.
Bengali and English.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Press coverage -- Indexes; Bangladesh -- History -- Revolution, 1971 -- Foreign public opinion